EFEK SENAM OTARIA TERHADAP KADAR Catalase PADA IBU POST PARTUM - Suhrawardi Suhrawardi; Ahmad Rizani; Rafidah Rafidah; Efi Kristiana (Sekolah Tinggi Pariwisata Mataram, 2023)
Uterine involution in postpartum mothers is influenced by many factors, one of which is physical activity, namely postpartum exercise or postpartum exercise (if the mother is healthy) which aims to reduce infections that occur in uterine involution caused by remaining blood that is not expelled, reducing the risk of abnormal bleeding. and to avoid blood clots that block veins. The implementation of this research was carried out by providing Otaria post partum exercise treatment in the intervention group and no post partum exercise treatment in the control group for 7 days. The design used in this research was Post Test Only Control Group Design or post test with experimental and control groups. The histogram shows that the average CAT levels increased in the treatment group, namely post partum mothers who carried out the Otaria exercise. In the control group, the average CAT levels appeared to decrease, namely post partum mothers who did not do Otaria exercises. Post partum mothers who did not do Otaria exercises had a decrease in CAT levels. The post partum period is a condition that is vulnerable to all kinds of stress. This is the result of physiological changes and metabolic functions since the beginning of pregnancy and fatigue during childbirth, causing oxidative reactions to increase to produce the energy needed by women in the post partum period. Oxidative stress in mothers during the post-partum period can be prevented by doing Otaria exercises which can increase CAT levels in post-partum mothers' plasma